Teamworking as practised by personnel in the Sarawak State Civil Service - Abdullah, Bibi Kasmawati (1999)
This study aims to find out whether the officers of the Sarawak State Civil Service perceive that they are practicing team working. Team working is achieved if the officers agree that they practice the elements of team working in their work place. These elements are a set of clear goals, commitment, good leadership, trust, effective decision making, good conflict management, empowerment and communication. This study also seeks to find out whether demographic variables such as age, gender, length of service, the officer's designated post and their ethnicity have any relationship to team working. The study was based on a survey research design using both the descriptive and inferential statistics. Senior officers from N3 or equivalent and above and officers from the Supervisory/Support group who had undergone the team building programs organized by the State Government formed the population of the study. Respondents for this study numbered 245 persons. The Preziosi's Organization Development Questionnaires (ODQ) (Preziosi, 1980) was used to gather data from the respondents. These questionnaires were mailed to officers if their working stations were outside the Kuching district and by hand delivered if they were in the same district. The analysis of the ODQ revealed that overall team working was practiced by these officers and that its level was high. However, elements of conflict management and decision making were moderately practiced by officers in the service.